HUBUNGAN MORALITAS DAN STATUS EKONOMI DENGAN KECERDASAN SOSIAL PADA REMAJA DI SMP NEGERI 9 BINJAI - Ali Muryati; Cut mutia (Universitas Medan Area, 2010)
The study was conducted to test whether there is a relationship of morality and economic status in adolescents with social intelligence on Junior High School 9 Binjai. Population of 700 adolescents aged 13 -15, which is used as a sample of 100 students, because all questionnaires were returned after completed. The results obtained are as follows great relationship X1 variable to variable Y, can be seen from the coefficient of determinant (R Square) = 0.229, indicating that 22.9% of social intelligence related to morality. Relationship variables X2 to Y, can be seen from the coefficient of determinant (R Square) = 0.202, indicating that 20.2% of social intelligence related to economic status. Correlation coefficient of the results showed that a significant relationship between the morality of social intelligence in adolescents with t count value = 8.751. While the t table = 1.984 for a significant level of 0.05 (5%), for 0.01 confidence level (1%) means the relationship between morality with social intelligence is very significant alevel of 0.05 and 0.01.Tthe relationship variables X1 and X2 to Y, can be seen determinant (R Square) = 0.662, indicating that 66.2% of social intelligence relating to morality and economic status.